The effect of lateral run training, zig-zag run training and motivation practice on player’s agility women’s football - Gusril; Ai Syah Putri; Willadi Rasyid; Padli (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
Based on the observation of the researcher is the low motivation to practice and the low agility of the female player Rajawali Football Club Padang The purpose of this study was effect of lateral run training, zig-zag run training, and motivation practice on player’s agility rajawali women’s football club Padang. This type of research is a quasi-experimental method that uses treatment with a Level 2 x 2 design, namely a factorial experiment involving two factors. The sample of this research is the female player Rajawali FC Padang who is 17 years old, totaling 20 people. Motivation practice data was measured using a questionnaire, and to measure football agility using the Illinois Agility test, then continued with testing requirements analysis of variance and data analysis using variance (ANAVA) 2 x 2. The results of data analysis showed that: (1) There was no difference in the effect of the lateral run training form and the zig-zag run training on the agility soccer players, (2) There was no interaction between the lateral run training, zig-zag run training and the player’s motivation on the agility soccer players.